Skrining Fasciolosis Pada Hewan Qurban Di Palangka Raya - Febri Nur Ngazizah; Meyta Wulandari; Rizka Hasanah (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2023)
Fasciola sp. a parasite which impacts ruminants including cattle, cause of the zoonotic disease fascioliosis. This study aims to describe the fasciolosis parasite in sacrificial animals on the Palangka Raya University campus in July–August 2023. This research is a descriptive exploratory study by examining the feces and livers of 15 samples of sacrificial animals with native methode. The results of the diagnosis of fasciolosis are based on the presence of Fasciola sp. eggs in the feces of sacrificed animals and the discovery of the parasite Fasciola sp. in the liver during post-mortem examination. The development of liver lesions in the form of inflammation and calcification brought on by the existence of Fasciola sp. was a defining characteristic of positively infected liver samples by worm infestations. Fasciola sp. eggs were found in the fecal samples with ovoid morphological characteristics, having an operculum at one pole, thin and smooth walls, and yellowish brown. The presence of Fasciola sp. being influenced by environmental factors, it is also heavily influenced by management factors, the majority of breeders in Palangka Raya take grass in watery areas where there are snails as intermediate hosts. This information can be a recommendation to the livestock service and to breeders to provide feed that is free of hosts and metacercariae of Fasciola sp. in Palangka Raya City.